Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Pada Rumah Sakit Umum Daerah Kota Cilegon - Mahfudhoh, Mahfudhoh; Muslimin, Ikhwanul (Jurnal Ilmiah Manajemen Kesatuan, 2020)
The hospital is a public facility owned by the government and the private sector which has a very strategic role in efforts to improve public health services. The new health care paradigm requires hospitals to provide quality services according to the needs and desires of patients while still referring to the professional and medical code of ethics. In the rapid development of technology and increasingly fierce competition, the hospital is required to improve the quality of its services. Quality is the core survival of an institution. Therefore, hospitals are required to always maintain consumer confidence by increasing the quality of service so that customer satisfaction increases. This study aims to analyze the influence of service quality on patients satisfaction. The research method used in this study is a survey method with correlation techniques. Data collection techniques using observation, interviews, and questionnaires (questionnaire). The results showed that the analysis of variable X obtained an average of 3.55, meaning that the quality of service at the Regional General Hospital (RSUD) of Cilegon City was in the Good category of 72.67%. Analysis of variable Y obtained an average of 3.50, which means that patient satisfaction at the Regional General Hospital (RSUD) of Cilegon City is in the good category of 70.1%. Analysis of product moment coefficient obtained r = 0.511 means that it has a moderate correlation between variable X and variable Y. The relationship pattern of variables is shown by a simple linear regression equation that is Y = 14.614 + 0.563 X. It shows that the variance that occurs in the variable quality of service can affect performance by 26%, while the remaining 74% is influenced by other factors not examined. Keywords : service quality, patient satisfaction, hospital